2017
DOI: 10.5194/esurf-2017-49
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Terrestrial laser scanning for quantifying small-scale vertical movements of the ground surface in Artic permafrost regions

Abstract: Abstract. Three-dimensional data acquired by terrestrial laser scanning (TLS) provides an accurate representation of Earth's surface, which is commonly used to detect and quantify topographic changes on a small scale. However, in Arctic permafrost regions the tundra vegetation and the micro-topography have significant effects on the surface representation in the captured dataset. The resulting spatial sampling of the ground is never identical between two TLS surveys. Thus, monitoring of heave and subsidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Warming of permafrost over the last few decades has been reported from many circum-Arctic boreholes (Biskaborn et al, 2019;Romanovsky et al, 2010). Warming and thawing of permafrost and an overall reduction in the area that it covers have been predicted under future climate change scenarios by the CMIP5 climate models, but at widely varying rates (Koven et al, 2012;McGuire et al, 2018). Continued observations, not only of the thermal state of permafrost but also of the multiple other types of data required to understand the changes to permafrost, are therefore of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Warming of permafrost over the last few decades has been reported from many circum-Arctic boreholes (Biskaborn et al, 2019;Romanovsky et al, 2010). Warming and thawing of permafrost and an overall reduction in the area that it covers have been predicted under future climate change scenarios by the CMIP5 climate models, but at widely varying rates (Koven et al, 2012;McGuire et al, 2018). Continued observations, not only of the thermal state of permafrost but also of the multiple other types of data required to understand the changes to permafrost, are therefore of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Sci. Data Discuss., https://doi.org/10.5194/essd-2018-82 from the scan positions as the incidence angle from the TLS instrument has a direct effect on 860 the penetration depth of the laser beam (Marx et al, 2017).…”
mentioning
confidence: 99%
“…Eltner and Baumgart (2015) reported that small elevation changes as a result of erosion and deposition can be detected by multitemporal TLS. The smallest changes detected reliably in their study were 1.5 10 2 m. With the exception of Marx et al (2017), no studies of TLS measurements of surface elevation changes smaller than a centimetre have been found for on-field experiments.…”
Section: Introductionmentioning
confidence: 90%
“…The smallest changes detected reliably in their study were 1.5×10 −2 m. With the exception of Marx et al. (), no studies of TLS measurements of surface elevation changes smaller than a centimetre have been found for on‐field experiments.…”
Section: Introductionmentioning
confidence: 99%